Longitudinal Analysis of Dengue Virus–Specific Memory T Cell Responses and Their Association With Clinical Outcome in Subsequent DENV Infection - Sanchez-Vargas, Luis Alberto; Anderson, Kathryn B.; Srikiatkhachorn, Anon; Currier, Jeffrey R.; Friberg, Heather; Endy, Timothy P.; Fernandez, Stefan; Mathew, Anuja; Rothman, Alan L. (Frontiers in Immunology, 2021)
Memory T cells resulting from primary dengue virus (DENV) infection are hypothesized to influence the clinical outcome of subsequent DENV infection. However, the few studies involving prospectively collected blood samples have found weak and inconsistent associations with outcome and variable temporal trends in DENV-specific memory T cell responses between subjects. This study used both ex-vivo and cultured ELISPOT assays to further evaluate the associations between DENV serotype-cross-reactive memory T cells and severity of secondary infection. Using ex-vivo ELISPOT assays, frequencies of memory T cells secreting IFN-γ in response to DENV structural and non-structural peptide pools were low in PBMC from multiple time points prior to symptomatic secondary DENV infection and showed a variable response to infection. There were no differences in responses between subjects who were not hospitalized (NH, n=6) and those who were hospitalized with dengue hemorrhagic fever (hDHF, n=4). In contrast, responses in cultured ELISPOT assays were more reliably detectable prior to secondary infection and showed more consistent increases after infection. Responses in cultured ELISPOT assays were higher in individuals with hDHF (n=8) compared to NH (n=9) individuals before the secondary infection, with no difference between these groups after infection. These data demonstrate an association of pre-existing DENV-specific memory responses with the severity of illness in subsequent DENV infection, and suggest that frequencies of DENV-reactive T cells measured after short-term culture may be of particular importance for assessing the risk for more severe dengue disease.